STAKEHOLDERS, SOCIAL RESPONSIBILITY AND REMUNERATION PRACTICES IN THE MALAYSIAN TOURISM SMALL AND MEDIUM-SIZED ENTERPRISES - Nurhazani MOHD SHARIFF (Geo Journal of Tourism and Geosites, 2020)
The tourism small and medium-sized enterprises play a vital role as the backbone in the Malaysian tourism industry, hence becoming a significant portion of entrepreneurial enterprises for the country. It is therefore essential for the enterprises to efficiently perform particularly in their managerial aspects. A study was conducted among 229 employees of the tourism small and medium-sized enterprises in Malaysia to investigate three major managerial practices namely, the stakeholders practice, the social responsibility practice and the remuneration practice in line with a better performance of the enterprises. The findings highlight that all three practices are considered as vital component in managing the tourism small and medium-sized enterprises. Majority of the respondents agreed that the stakeholders of the enterprises would establish fair procedures for goods and services based on considerations of quality, pricing and performance. Further, most of them also agreed that environmental management is essential as their social responsibility practice in the enterprises. Additionally, the findings indicate that most respondents found that the incentive of top management in the enterprises would ensure the alignment of the management and stakeholders’ interest. The study significantly contribute to the tourism small and medium-sized enterprises in creating better management scenario within the enterprises in order to achieve strategic planning competitiveness in the industry.